Problems of the modern Middle East in historical perspective essays in honour of Albert Hourani - Spagnolo, John P; Hourani, Albert, d 1915-1993 (Published for the Middle East Centre, St. Antony's College, Oxford by Ithaca Press, 1992)
The late Albert Hourani was the leading European historian of the Middle East. Former director of the Middle East Centre at St Antony's College, Oxford, he was widely known and respected for his numerous writings on the Middle East and Islam. This book is a collection of historical studies on the Middle East by some of Albert Hourani's leading students and colleagues